Changing role of state in a globalised economy: case study on Malaysia- India companies - Suseela Devi Chandran; Rashila Ramli (Universiti Kebangsaan Malaysia, 2015)
Globalisation has a significant impact on the role of nation-state. Hyper globalists, sceptics, and liberals in the realm of international relations theory, contend that globalisation renders the state irrelevant, diminishes the state’s role, and erodes state power. The objective of this study is to analyse the impact of globalisation on companies in Malaysia and India. This article presents four case studies of companies operating in Malaysia and India to determine the impact of globalisation as well as evaluating the role of state and private sectors in moving forward economic cooperation. Given the structure of the goods and services trade between Malaysia and India, some analysts argue that the onus will be on the private sector to carry economic relations forward. This paper advocates that Malaysia strives to adopt a pragmatic approach, by trying to strike a balance between state intervention and withdrawal in economic matters, in order to achieve specific ends without affecting political stability and economic growth. In the case of Malaysia-India economic relations, it is apparent that the state is not only an important actor, but also a key driver. Indeed, the state is seen as a major supporter and beneficiary of economic and technological advances. Although challenges persist in terms of government regulations, bureaucratic red tape and state government policies, nevertheless business continues to thrive.